2020
DOI: 10.1177/0194599820943530
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction in COVID‐19 Patients: Prevalence and Prognosis for Recovering Sense of Smell

Abstract: While olfactory dysfunction associated with coronavirus disease 2019 (COVID-19) has attracted considerable interest, few studies have tracked outcomes at serial time points or beyond 2 weeks. Furthermore, data are conflicting regarding whether COVID-19 severity correlates with degree of olfactory dysfunction. This prospective case-control study analyzed prevalence and severity of subjective loss of smell in outpatients (n = 23) and inpatients (n = 20) with confirmed severe acute respiratory syndrome coronaviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
4
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 29 publications
7
76
4
4
Order By: Relevance
“…A total of 11074 COVID-19 patients (mean age 46.7±10.4 years and males 46.9%) were included in the final analysis ( table 1 ). 2 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 The overall prevalence of “loss of smell” in COVID-19 patients was 52.0% (CI: 42.5%-61.6%, I 2 =99.4%) ( Figure 2 ). A total of 21 studies compared these symptoms in COVID-19 patients (n=2196) and controls (n=3425).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 11074 COVID-19 patients (mean age 46.7±10.4 years and males 46.9%) were included in the final analysis ( table 1 ). 2 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 The overall prevalence of “loss of smell” in COVID-19 patients was 52.0% (CI: 42.5%-61.6%, I 2 =99.4%) ( Figure 2 ). A total of 21 studies compared these symptoms in COVID-19 patients (n=2196) and controls (n=3425).…”
Section: Resultsmentioning
confidence: 99%
“…Among COVID-19 patients, the odds of patients with severe disease and “loss of smell” were significantly low when compared to patients with severe disease and without “loss of smell” (OR: 0.36, CI 0.27–0.48, p <0.01, I 2 =27.4% ( Figure 4 ). 2 , 21 , 32 , 37 , 52 , 54 , 57
Figure 2 Forest plot demonstrating overall prevalence of “loss of smell” in COVID-19 patients.
Figure 3 Forest plot comparing prevalence in COVID-19 vs control group for “loss of smell”.
…”
Section: Resultsmentioning
confidence: 99%
“…In total, 78 studies were included to calculate the prevalence of headache in COVID-19 and all studies were published in 2020. The studies were conducted in Brazil 50 , China 13,51-96 , Egypt 97 , France 98-101 , Germany 102 , India 103,104 , Italy [105][106][107][108][109][110][111] , Japan 112,113 , Jordan 114 , Somalia 115 , South Korea 116,117 , Spain 118,119 , Turkey 120,121 , and the US [122][123][124][125][126] . Two studies were cross-sectional 119,122 , five were prospective cohort studies 65,90,98,110,121 and the remaining 71 studies were retrospective studies.…”
Section: Study Eligibility Resultsmentioning
confidence: 99%
“…In our follow-up period, a mean of 59.2 days after the second negative PCR test, we found that OD had resolved in 64.9% of the patients and none reported residual nasal obstruction. Our analysis is characterized by a relatively long follow-up period and high percentage of residual OD compared to reports in the literature (3,4,12,(14)(15)(16) and provides a complementary data regarding the clinical course of OD and GD.…”
Section: Discussionmentioning
confidence: 91%
“…Few studies have tracked outcomes at serial time points and have shown a gradual improvement in olfactory and gustatory functions over time. (3,4) Further analysis by Paderno et al. (4) found nasal congestion, gender, and grade of dysfunction, as risk-factors for late resolution from OD.…”
Section: Introductionmentioning
confidence: 99%